Strategi Lobi & Negosiasi dalam Pembangunan Waterfront City: Studi Kasus Reklamasi Pantai Karangria, Kota Manado - Zahra, Cut Salwa Alifia; Majida, Iqlima Ghaitsa; Wulandari, Lia (Majalah Ilmiah METHODA, 2025)
This study examines lobbying and negotiation strategies within the development of the Waterfront City project in Karangria Beach, Manado City, which sparked conflict between the government and coastal communities. The main issue lies in the imbalance of power and interests among stakeholders, including the Manado City Government, the developer PT Manado Utara Perkasa, fishermen communities, environmental NGOs, and the general public. The aim is to analyze lobbying and negotiation approaches undertaken by project proponents to gain public legitimacy and reduce resistance. This research employs a qualitative, descriptive-analytical method using literature review as the primary data collection technique. Findings indicate that stakeholder mapping using the power-interest grid and the prominence model is effective in formulating contextual strategies. The government and developers hold dominant power, while local communities face high urgency but limited influence. Thus, project success relies heavily on communication strategies, inclusive engagement, and the fulfillment of promises made to affected groups.